1998
DOI: 10.1046/j.1365-2796.1998.00315.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia monitoring with on‐line vectorcardiography during dobutamine stress echocardiography in patients after an episode of unstable coronary artery disease

Abstract: Abstract. Lundin P, Eriksson SV, Andrén B, Lindahl B, Tor nvall P, Melcher A (Danderyd Hospital, Danderyd, University Hospital, Uppsala, Karolinska Hospital, Stockholm, Sweden). Ischaemia monitoring with on-line vectorcardiography during dobutamine stress echocardiography in patients after an episode of unstable coronary artery disease. J Intern Med 1998; 244: 61-70.Objectives. This study investigated the ability of online vectorcardiography (VCG) to detect myocardial ischaemia as assessed by dobutamine stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Steg et al [18] showed that ST changes induced by transient coronary occlusion in humans were related to scintigraphic quantitative indexes of myocardial ischaemia, but the correlation was mostly with the severity of ischaemia rather than with the size of the area at risk. Lundin and co-workers [19] found STC-VM to be related to ischaemia, as assessed by dobutamine stress echocardiography. Patients with a positive dobutamine stress test showed higher maximum STC-VM values than patients with a negative dobutamine stress test.…”
Section: Discussionmentioning
confidence: 98%
“…Steg et al [18] showed that ST changes induced by transient coronary occlusion in humans were related to scintigraphic quantitative indexes of myocardial ischaemia, but the correlation was mostly with the severity of ischaemia rather than with the size of the area at risk. Lundin and co-workers [19] found STC-VM to be related to ischaemia, as assessed by dobutamine stress echocardiography. Patients with a positive dobutamine stress test showed higher maximum STC-VM values than patients with a negative dobutamine stress test.…”
Section: Discussionmentioning
confidence: 98%
“…In multivariate analysis, reduction of ST-segment elevation was the only independent predictor of functional recovery (30). One study indicated that on-line VCG may predict ischemia in the predischarge exercise test (31) as well as ischemia in dobutamine stress echocardiography (32). This finding is interesting since recent trials have indicated that not all patients with acute MI should follow an invasive strategy including routine angiography followed by revascularization if feasible (33,34).…”
Section: On-line Vectorcardiographymentioning
confidence: 99%